A Deixis Analysis Song Lyric of “ Reckless” By Madison Beer - Elvina Rosa Dilla; Foury Widya Anjani; Indahh Rustiyani; Syafa Salsabila Putri Annazmi; Emeliya Sukma Dara D (e-Journal of Linguistics, 2023)
This study aim of the research is to identify the type ofdeixis and the dominant type of deixis in the lyrics ofMadison Beer's song Reckless. This study is a type ofqualitative research. Data collection techniques includelistening to songs and analyzing Madison Beer's song"Reckless." The findings of this study include all types ofdeixis found in the person (64 data), spatial (11 data),temporal (8 data), and social (5 data) deixis found in thelyrics of Madison Beer's song Reckless. People's deixis ismost frequently found in Reckless lyrics. The majority ofthe deixis found in this study are people's deixis, such as Iand You. While the plural deixis of people found is Wewhich is addressed to the listener.